Allelopathic effect of Abuthilon theophrasti Med. extracts on germination of maize seed - Konstantinović Bojan (Proceedings of the International Symposium on Analytical and Environmental Problems, 2018)
During 2014 allelopathic effects of Abutilon theophrasti Med. water extracts to germination and initial development of maize (Zea mays L.), were studied in laboratory conditions. In addition to the Water extracts out of dry mass of the tested weed species, the applied concentrations were 1 g/l, 2 g/l, 4 g/l of dry matter made out of weed species in the 3-4 leaf stage of development. Water solution of A. theophrasti showed inhibitory effect on maize seed epicotyls and hypocotyls length. The applied extracts made out of dry matter of the studied weed species A. theophrasti reduced maize seed germination for 9%-14% in comparison to the control in which it was 88%. After germination in a climate chamber, epicotyls’ and hypocotyls’ length of maize seeds was measured three, six and ten days following spraying by extracts.